Ultrasonication an intensifying tool for preparation of stable nanofluids and study the time influence on distinct properties of graphene nanofluids – a systematic overview - Sandhya, Madderla; D., Ramasamy; K., Sudhakar; K., Kadirgama; W. S. W., Harun (Elsevier Ltd, 2021)
Optimum ultrasonication time will lead to the better performance for heat transfer in addition to preparation methods and thermal properties of the nanofluids. Nano particles are dispersed in base fluids like water (water-based fluids), glycols (glycol base fluids) &oils at different mass or volume fraction by using different preparation techniques. Significant preparation technique can enhance the stability, effects various parameters & thermo-physical properties of fluids. Agglomeration of the dispersed nano particles will lead to declined thermal performance, thermal conductivity, and viscosity. For better dispersion and breaking down the clusters, Ultrasonication method is the highly influential approach. Sonication hour is unique for different nano fluids depending on their response to several considerations. In this review, systematic investigations showing effect on various physical and thermal properties based on ultrasonication/ sonication time are illustrated. In this analysis it is found that increased power or time of ideal sonication increases the dispersion, leading to higher stable fluids, decreased particle size, higher thermal conductivity, and lower viscosity values. Employing the ultrasonic probe is substantially more effective than ultrasonic bath devices. Low ultrasonication power and time provides best outcome. Various sonication time periods by various research are summarized with respect to the different thermophysical properties. This is first review explaining sonication period influence on thermophysical properties of graphene nanofluids.